Hepatic Microwave Ablation in Challenging Locations - Smolock, Amanda R.; Shaw, Colette (Seminars in Interventional Radiology, 2019)
In recent years, there has been increased utilization of microwave ablation (MWA) in the treatment of soft tissue tumors. MWA has several theoretical advantages over radiofrequency ablation (RFA) by achieving a more rapid and sustained heating of tissues, increased efficacy in tissues with poor thermal conductivity, and less susceptibility to heat sink effect. While its greater power output has led to appropriate caution when applying this energy to soft tissue tumors, many commonly held beliefs regarding contraindications to MWA are unsupported by data and have been passed along based on experience with RFA. The goal of this article is to review the use of MWA in challenging clinical situations along with the existing evidence for its use.
Keywords: microwave ablation; tumor ablation; liver transplant; contraindications